ANALISIS SINYAL WIRELESS DENGAN MAPPING SSID DAN HOTSPOT AREA ACCESS POINT DENGAN METODE PPDIOO DI SMK NEGERI 2 PRAYA TENGAH - Rudi Setiawan, L (Pusat Riset dan Inovasi Nasional, 2022)
The Final Semester Exam at SMK Negeri 2 Praya Tengah still uses a manual exam system, namely using paper and stationery, this requires more time and cost than using a computer/android-based exam system. Currently, SMK Negeri 2 Praya Tengah is in the migration stage from manual semester exams to web/computer-based semester exams, but the quality and signal strength of the internet network at SMK Negeri 2 Praya Tengah is influenced by various kinds of obstacles (interference) and improper location of access point placement. So that the internet network at SMK Negeri 2 Praya Tengah often experiences buffering, disconnected from the internet network and signals with weak strength. From the problems obtained related to the strength and quality of the internet network signal at SMK Negeri 2 Praya Tengah, a wireless signal analysis was carried out using the PPDIOO method to determine the area of the building with a weak or poor signal. The PPDIOO method is a network life cycle consisting of 6 stages: prepare, plan, design, implement, operate and optimize. This study aims to analyze the existing network at SMK Negeri 2 Praya Tengah in order to find out how the signal coverage is from each access point installed in each building at SMK Negeri 2 Praya Tengah.